SUMO-2 and PIAS1 Modulate Insoluble Mutant Huntingtin Protein Accumulation. - O'Rourke, J.G.; Gareau, J.R.; Ochaba, J.; Song, W.; Raskó, T.; Reverter, D.; Lee, J.; Monteys, A.M.; Pallos, J.; Mee, L.; Vashishtha, M.; Apostol, B.L.; et al. (Cell reports, 2013)
A key feature in Huntington disease (HD) is the accumulation of mutant Huntingtin (HTT) protein, which may be regulated by posttranslational modifications. Here, we define the primary sites of SUMO modification in the amino-terminal domain of HTT, show modification downstream of this domain, and demonstrate that HTT is modified by the stress-inducible SUMO-2. A systematic study of E3 SUMO ligases demonstrates that PIAS1 is an E3 SUMO ligase for both HTT SUMO-1 and SUMO-2 modification and that reduction of dPIAS in a mutant HTT Drosophila model is protective. SUMO-2 modification regulates accumulation of insoluble HTT in HeLa cells in a manner that mimics proteasome inhibition and can be modulated by overexpression and acute knockdown of PIAS1. Finally, the accumulation of SUMO-2-modified proteins in the insoluble fraction of HD postmortem striata implicates SUMO-2 modification in the age-related pathogenic accumulation of mutant HTT and other cellular proteins that occurs during HD progression.